Pipelines 2016 : out of sight, out of mind, not out of risk : proceedings of the Pipelines 2016 Conference, July 17-20, 2016, Kansas City, Missouri - Livingston, Byron, L.; Cate, Cliff, III; Pridmore, Anna B.; Heidrick, Jeffrey W.; Geisbush, Jim (Published by American Society of Civil Engineers, 2016)
"This collection contains 177 peer-review papers on the growing need to properly design, operate, and maintain pipeline infrastructure. Topics include: planning and design; condition assessment; rehabilitation; corrosion; fast-track designs; surveying and jurisdictional issues; and natural disaster mitigation"-- ASCE website
"Sponsored by Utility Engineering and Surveying Institute of the American Society of Civil Engineers."
Keywords: Pipelines -- Design and construction -- Congresses.; Pipelines -- Maintenance and repair -- Congresses.; elektronické knihy; electronic books